Painful Memories: Reliability of Pain Intensity Recall at 3 Months in Senior Patients - Raoul Daoust; Marie-Josée Sirois; Jacques S. Lee; Jeffrey J. Perry; Lauren E. Griffith; Andrew Worster; Eddy Lang; Jean Paquet; Jean-Marc Chauny; Marcel Émond (Pain Research and Management)
Background. Validity of pain recall is questioned in research. Objective. To evaluate the reliability of pain intensity recall for seniors in an emergency department (ED). Methods. This study was part of a prospective multicenter project for seniors (≥65 years old) treated in an ED for minor traumatic injury. Pain intensity (0–10 numerical rating scale) was evaluated at the initial ED visit, at one week (baseline), and 3 months. At three months, patients were asked to recall the pain intensity they had at baseline. Results. 482 patients were interviewed (mean age 76.6 years, SD ± 7.3) and 72.8% were female. Intraclass correlation coefficient between pain at baseline and its recall was 0.24 (95% CI: 0.14–0.33). Senior patients tended to overestimate their pain intensity by a mean of 1.2 (95% CI: 0.9–1.5) units. A stepwise multiple regression analysis showed that the variance of baseline pain recall at 3 months was explained by pain at ED visit (11%), pain at 3 months (7%), and pain at baseline (2%). Conclusion. The accuracy of pain intensity recall after three months is poor in seniors and seems to be influenced by the pain experienced at the time of injury.